The Nasikh dan Mansukh dalam Al-Qur’an: Nasikh dan Mansukh dalam Al-Qur’an - Hazyimara, Karunia (CV Kalimasada Group, 2023)
The Qur'an as a guide of Muslims has a fairly high concern by scholars. There are views that some verses in the Qur'an are contradictory, so that this leads to the study of nasikh-mansukh. The study is not necessarily accepted by all scholars or observers of Qur'anic science, because according to them there can be no revision in the Qur'an. This research tries to discuss nasikh-mansukh studies both related to understanding, differences of opinion, orientalist views to the wisdom of studying them using qualitative methods from library data. This study found that differences of opinion in the scholarly environment occurred due to differences in the roots of their studies. With the nasikh-mansukh theory one can understand why there are verses that textually seem contradictory.